SEM-Based Analysis of Electromagnetic Logging Sensors for Oil Wells in Geophysical Formations - Ribeiro, Raul O. [UNESP]; Rosa, Guilherme S. [UNESP]; Penchel, Rafael A. [UNESP]; Bergmann, Jose R.; Teixeira, Fernando L. (My University, 2024)
This work introduces a new formulation for modeling electromagnetic well-logging sensors using the higher-order spectral element method. The approach utilizes the Lorentz reciprocity theorem to determine the total field generated by practical sources. Horizontal coil antennas are used for both the sensor's transmitter and receiver. The method is tested in an oil invasion zone scenario, and preliminary results align well with the mode-matching technique reference solutions.